The Role of Wood Vinegar in Enhancing the Microbial Activity and Physicochemical Properties of Palm Oil-Based Compost - Nor Hanuni, Ramli; Nur Eliza, Badrul Hisham; Farhan, Mohd Said; Nur Ezyan, Badrul Hisham; Olalere, Olusegun Abayomi (Universiti Putra Malaysia Press, 2019)
This paper presents an experimental study of the effect of wood vinegar at different concentrations on the biological and physicochemical properties of the composts by using the solution with the ratio of wood vinegar to distilled water in the range of 1:100 to 1:500 (v/v). The composting process was conducted by in-vessel composting method within 60 days where temperature and pH were recorded daily. The composts were then analyzed on the microbe counts, pH, moisture content, water holding capacity, and nutrient contents. XRF and CHNS analyzers were used to measure the NPK content exist before and after composting process. This research attempted to investigate the effect of wood vinegar concentration towards physiochemical and biological properties of the composts. The results showed that lower concentration of wood vinegar could potentially enhance microbial activity which could accelerate the composting process. However, in terms of physical properties, sample 1:400 (v/v) had recorded the highest reading for water holding capacity and moisture content which were about 2 to 19 % (ml/100g) and 1 to 27 % (w/w) higher than other samples, respectively. Therefore, it can be concluded that sample 1:400 (v/v) shows the best condition where it has achieved well-balanced condition between physicochemical and biological properties.